2012
DOI: 10.1007/s00402-012-1514-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cephazolin, ceftazidime, and ceftriaxone distribution in nucleus pulposus

Abstract: The antibiotics of cephazolin, ceftazidime, and ceftriaxone had concentration in the NP tissue, which was higher than the stated MIC. Ceftazidime had highest penetration in to NP tissue, and ceftriaxone had the lowest penetration in to NP tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2031
2031

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Finally, ceftazidime 2 g reached tissue/plasma ratios of 0.03–0.08X in lower limb bone tissues of 10 patients who underwent amputation [ 76 ]. The penetration of cefazolin, ceftazidime or ceftriaxone (2 g each) into the nucleus pulposus of 22 patients undergoing elective vertebral surgery was always lower than 0.06X 60 min after drug administration [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, ceftazidime 2 g reached tissue/plasma ratios of 0.03–0.08X in lower limb bone tissues of 10 patients who underwent amputation [ 76 ]. The penetration of cefazolin, ceftazidime or ceftriaxone (2 g each) into the nucleus pulposus of 22 patients undergoing elective vertebral surgery was always lower than 0.06X 60 min after drug administration [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gibson et al 41 found no detectable levels of flucloxacillin or cephadrine in the discs of adolescents undergoing scoliosis surgery and in an animal model Fraser et al 42 found very low levels of cephazolin in the disc 30 min after administration, becoming undetectable at 60 min. More recently, several studies [43][44][45][46] have found measureable levels of cephalosporins in the majority of discs although not necessarily in concentrations above the minimum inhibitory concentration to prevent S. aureus growth. It has been argued that the internal structure of the disc plays an important role in its permeability.…”
Section: Resultsmentioning
confidence: 99%
“…They receive their nutrition and get rid of waste products via the process of diffusion 1 . This diffusion depends on several factors which include, among others, drug molecular charge, protein binding, serum concentration, time after administration and disc degeneration [5][6][7]10,22 . For the antibiotic to be effective in preventing infection, it must penetrate into the disc in a concentration above the minimal inhibitory concentration (MIC) of the causative bacteria 23 .…”
Section: Discussionmentioning
confidence: 99%
“…If antibiotics do not reach the inner part of the disc (nucleus pulposus, NP) in a sufficient concentration that exceeds the minimal inhibitory concentration (MIC) of the causative micro-organism, it may not protect against infections during discectomy and may result in discitis and failure of operation 2 . Several antibiotics were found to have good penetration into the intervertebral disc such as ceftriaxone, ceftazidime and cefazolin [3][4][5][6] , cefuroxime & gentamicin [7][8] , clindamycin and tobramycin [9][10] , vancomycin 11 and several others. On the other hand, antibiotics like linezolid 12 , ciprofloxacin, co-amoxiclav and amoxicillin 13,14 , cefalothin 9 , and cefradine and flucloxacillin 14 had intermediate or low penetration.…”
Section: Introductionmentioning
confidence: 99%